Necrotizing Fasciitis Post-Cesarean Section Leading to Transabdominal Hysterectomy - Alvina Liang; Mary Boluwatife Idowu; Steven Joseph Eskind; Soha S. Patel (Thieme Medical Publishers, Inc., 2024)
Necrotizing fasciitis (NF) is a rare but life-threatening disease characterized by rapidly spreading inflammation and subsequent necrosis of the fascial planes and surrounding tissues. Limited literature has described NF as involving an adjacent solid organ beyond fascial planes that has required its removal. We present a case of a 25-year-old white female who underwent a cesarean section and subsequently developed NF involving her uterus and abdominal wall that necessitated a total abdominal hysterectomy, serial surgical debridement of necrotic tissue, and wound vacuum assisted closure (VAC) placement. Her pathology report described her uterus infiltrated by polybacteria, confirming a diagnosis of NF. Despite NF's progressive nature and potential lethality, NF can be challenging to diagnose clinically due to a lack of pathognomonic signs and symptoms. However, early detection of NF with the aid of Laboratory Risk Indicator for Necrotizing Fasciitis score calculation using laboratory values such as white blood cell count, hemoglobin, sodium, glucose, serum creatinine, and C-reactive protein is critical for optimal patient outcomes. A multidisciplinary team approach is vital in treating these patients to debride necrotizing tissue and control the potential sequelae from the infection, particularly for postpartum patients.